Phytoene and Phytoene-Rich Microalgae Extracts Extend Lifespan in C. elegans and Protect against Amyloid-β Toxicity in an Alzheimer's Disease Model - Ángeles Morón-Ortiz; Antonis A. Karamalegkos; Paula Mapelli-Brahm; Marina Ezcurra; Antonio J. Meléndez-Martínez (MDPI AG, 2024)
Phytoene is a colourless carotenoid widely available from dietary sources and a precursor for the synthesis of other carotenoids. Although present at high concentrations across different tissues, phytoene is largely viewed as not having physiological activity. Here, we utilize the model organism C. elegans to show that phytoene is bioactive and has anti-ageing properties. Supplementation with phytoene protects against oxidative damage and amyloid-β42 proteotoxicity (a major pathology of Alzheimer's disease), and extends lifespan. We also examine extracts from two microalgae, Chlorella sorokiniana and Dunaliella bardawil. We show that the extracts contain high levels of phytoene, and find that these phytoene-rich extracts have protective effects similar to pure phytoene. Our findings show that phytoene is a bioactive molecule with positive effects on ageing and longevity. Our work also suggests that phytoene-rich microalgae extracts can utilized to produce foods or supplements that promote healthy ageing and prevent the development of chronic age-related diseases.